2018
DOI: 10.3389/fncel.2018.00488
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in Neurological Diseases: A Road Map to Brain-Disease Dependent-Inflammatory Response

Abstract: Microglia represent a specialized population of macrophages-like cells in the central nervous system (CNS) considered immune sentinels that are capable of orchestrating a potent inflammatory response. Microglia are also involved in synaptic organization, trophic neuronal support during development, phagocytosis of apoptotic cells in the developing brain, myelin turnover, control of neuronal excitability, phagocytic debris removal as well as brain protection and repair. Microglial response is pathology dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
413
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(425 citation statements)
references
References 220 publications
(266 reference statements)
7
413
1
4
Order By: Relevance
“…In fact, the microglia exhibited increased metabolic upregulation from multiple energy sources. RNA sequencing of microglia in neurodegenerative disease has shown that microglial exhibit more nuanced states than these simple M1 and M2 polar opposites (14,85,(91)(92)(93). There is also evidence to suggest that dysregulation of metabolism and accumulation of mt-DNA mutations within microglia may itself be a trigger for microglial activation in neurodegenerative disease (94).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the microglia exhibited increased metabolic upregulation from multiple energy sources. RNA sequencing of microglia in neurodegenerative disease has shown that microglial exhibit more nuanced states than these simple M1 and M2 polar opposites (14,85,(91)(92)(93). There is also evidence to suggest that dysregulation of metabolism and accumulation of mt-DNA mutations within microglia may itself be a trigger for microglial activation in neurodegenerative disease (94).…”
Section: Discussionmentioning
confidence: 99%
“…However, microglia can mediate beneficial and detrimental neuroinflammatory mechanisms during disease. Indeed, because microglia are transcriptionally diverse and highly responsive to their environment (Dubbelaar et al, 2018), they contextually respond to acute and chronic tissues disease states determined by both the primary disease mechanism and disease duration (Bachiller et al, 2018; Tay et al, 2017). In general, detrimental consequences of microglial responses in AD are mediated by pro-inflammatory mechanisms, which include release of neurotoxic molecules (ROS, NO), production of cytokines (IL1β, TNFα, IL6), phagocytosis of live neurons or of healthy synapses and dendrites, impaired phagocytic clearance of debris and pathological protein aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of α -syn causes AST to produce pro-inflammatory cytokines and activate MG, suggesting a plausible role of AST in the initiation of PD 23, 24 . Given that AST and MG are two primary cell types that closely involved in neuroinflammation 43 , we next focused on AST and MG to explore the neuroinflammatory reactions at early stage of PD. Transcriptomic changes of MB_MG under pathological state were not compelling, with only 87 down-regulated genes and none up-regulated genes (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%